The effects of cultivation site on forage quality of Calliandra calothyrsus var. Patulul - Hess, H.D.; Tiemann, Tassilo T.; Noto, F; Franzel, Steven; Lascano Aguilar, Carlos Eduardo; Kreuzer, M. (Springer, 2006)
An in vitro experiment was performed to compare the forage quality of foliage of Calliandra (Calliandra calothyrsus Meissner var. Patulul) cultivated on either low or medium-fertility soils in Colombia and Kenya, respectively. A grass-alone diet, with and without urea supplementation, and five legume-supplemented diets (1/3 of dietary dry matter) were tested with the rumen simulation technique (Rusitec) (n = 4). The legume supplements consisted of Cratylia (Cratylia argentea), Calliandra from Colombia or Kenya, or 1:1 mixtures of Cratylia with Calliandra Colombia or Kenya. The tannin content of Calliandra Colombia was almost twice as high as that of Calliandra Kenya. Supplementation with urea or Cratylia alone, but not with Calliandra alone, increased ammonia concentration in the fermenter fluid. Unlike Calliandra Colombia, Calliandra Kenya in mixture with Cratylia increased ammonia concentration. The apparent degradation of organic matter increased with all types of supplementation, except with Calliandra Colombia alone. Although the foliage of Calliandra from the two cultivation sites had similar contents of organic matter, crude protein and neutral detergent fibre, they differed in?nearly all fermentation properties. The material from Kenya showed a higher apparent nutrient degradability. These results indicate that C. calothyrsus var. Patulul cultivated at the Kenyan site had a clearly higher forage quality than foliage from the same variety cultivated in Colombia. However, both materials had a much lower forage quality than Cratylia. The Cratylia-related effects on ruminal fermentation were mainly the results of an increased supply of fermentable nitrogenous compounds as was obvious from the comparison with the urea-supplemented grass.